The Relationship Between Vitamin D Deficiency and Bone Mineral Density Among Adults in Bani Walid, Libya (Scientific Journal for Publishing in Health Research and Technology, 2025)
Background and Objectives: Despite abundant sunlight, Vitamin D deficiency has become a pressing global public health concern, a situation increasingly evident in Libya, particularly in Bani Walid. This paradox is driven by factors such as limited outdoor activity, clothing styles that restrict sun exposure, and diets low in vitamin D-rich foods. Low vitamin D levels directly impair calcium absorption and bone mineralization, leading to reduced bone mineral density (BMD) and a higher risk of osteoporosis and fractures. This study aimed to investigate the prevalence of vitamin D deficiency among adults in Bani Walid, Libya, and determine the relationship between vitamin D status and BMD. The research also sought to assess if gender differences play a role in this association. Methods and Results: A cross-sectional study was conducted on 200 adult participants in Bani Walid, Libya, between May and September 2025. Serum vitamin D levels and BMD were assessed using standardized tests and Dual-Energy X-ray Absorptiometry (DEXA). The results showed that 52.0% of participants were vitamin D deficient, with an additional 28.0% having insufficient levels. Vitamin D levels were significantly lower among females (67.0%) compared to males (25.0%). Low BMD values were observed in 70.0% of the study population. Crucially, a strong positive correlation was found between low vitamin D levels and reduced bone density (p = 0.0001). Conclusion and Recommendations: The findings confirm that vitamin D deficiency is widespread and strongly associated with reduced BMD in Bani Walid adults. Addressing this deficiency through preventive strategies- such as regular screening, dietary supplementation, and lifestyle modifications-is an urgent public health priority to protect bone health in the adult population of Bani Walid and similar regions in Libya
Keywords: Vitamin D deficiency; bone mineral density; prevalence; adults; Bani Walid; Libya